A comparative analysis of intelligent and PID controllers for an aircraft pitch control system - Wahid, Herman (Applications of Modelling and Simulation, 2018)
Aircraft pitch control system is one example of nonlinear complex systems which requires feedback control. Fuzzy logic controllers (FLC) have emerged as intelligent method in controlling such system by utilizing fuzzy logic principle. This paper presents a comparative analysis for the performance of proportional-derivative-integral (PID) controller and fuzzy logic controller in controlling the aircraft pitch angle. The input is the elevator deflection angle and the output is the pitch angle of the aircraft. For the fuzzy controller, it is governed by five membership functions and seventeen rules which were tuned repeatedly according to the actual output of the controller corresponding to the customized set point. The procedures of the PID and the FLC design are discussed in methodology section. In general, both PID and FLC perform within the design requirements. However, FLC outperforms PID in three design parameters namely the settling time, the percentage of overshoot and the steady state error, with improvements of 12%, 98% and 97%, respectively.